Negative Pressure Wound Therapy in Surgical Wound Management: Mechanisms, Clinical Outcomes, and Comparative Analysis of Modern NPWT Systems - Piotr Marcjasz; Anna Bioły; Agnieszka Buliszak; Monika Babczyńska; Agnieszka Borończyk; Piotr Zając (Quality in Sport)
Introduction: Surgical wounds that fail to heal or that develop complications such as infection or dehiscence are challenging problem that health care has to deal with everyday. Negative Pressure Wound Therapy (NPWT) has emerged as an important tool for managing complex wounds. This review aims to summarize the mechanisms by which NPWT supports wound healing, estimate the clinical efficacy of NPWT in surgical wounds and compare available NPWT systems.